Psychometric evaluation of the Body Image Concern Inventory in an undergraduate sample. (29th August 2018) - Collison, James; Mahlberg, Justin
Abstract: Background: This study evaluated the psychometric properties of the Body Image Concern Inventory (BICI); a self‐report measure of dysmorphic appearance concern. Methods: Internal consistency, concurrent validity, and construct validity were investigated among 761 female undergraduates. Criterion validity was also investigated with respect to body dysmorphic disorder (BDD). Results: The BICI appears internally consistent and displayed predictable relationships to depression, anxiety, self‐esteem, functional impairment, and body image disturbance. Three factors appeared to underlie the BICI (i.e. appearance preoccupation, appearance concern, coping behaviour), accounting for 52.13%, 7.77%, and 5.80% of the observed variance. Further analysis revealed that nine items could be removed from the BICI without notable change to its validity or reliability. This resulted in a shorter version of the BICI that demonstrated improved factor structure and internal consistency, with equivalent degrees of concurrent and criterion validity. Neither measure operated effectively as a diagnostic screen for BDD, reflected by low sensitivity and specificity values. Conclusions: Both appear to be reliable and valid measures that should predominantly be employed as continuous measures of body image preoccupation.